From free speech advocates to critics: The Trump administration’s new rhetoric promotes support for censorship among Trump voters - Matthew E. K. Hall; B. Tyler Leigh; Brittany C. Solomon (Proceedings of the National Academy of Sciences, 2026)
Most Americans claim to support freedom of speech, including President Donald Trump who has portrayed himself as an ardent defender of this constitutional right. However, in the wake of Charlie Kirk’s assassination, Trump and members of his administration began to explicitly call for speech restrictions. This largely unprecedented rhetoric from a sitting president and his allies provides an opportunity to examine competing theories of public opinion: the influence of partisan elites versus the public’s purported commitment to free speech. In a preregistered survey experiment, we found that exposure to such unusually explicit antispeech rhetoric increased Trump voters’ support for government censorship of outparty media and individuals but prompted backlash among non-Trump voters, increasing their support for protecting outparty speech. While prior research has established that partisans favor censorship of outparty members, we demonstrate that partisans differentially shifted their censorship attitudes in response to the Trump administration’s new rhetoric, whether or not the source was attributed to Trump and his allies. These findings highlight the influence of elite rhetoric on public support for even the most foundational—and popular—democratic norm, raising concerns about the resilience of American democracy in the face of explicitly illiberal elites.